Protein Profile of Limousin Cows and F1 Crossbred with Limousin & Brahman Bulls - Nur Rohman, Mohamad Agung; Mudawamah (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Plasma protein profiles are important indicators that reflect the health, immunological, and physiological status of cattle in relation to their production and reproductive performance. The objective of this study was to determine the total and fractionated protein levels in the plasma of Indonesian Limousin cows and their F1 offspring. The study sample consisted of 15 animals, including Indonesian Limousin cows and their F1 calves. Blood plasma was analyzed in the laboratory using the biuret method (total protein), bromcresol green (albumin concentration), and globulin (difference between total protein and albumin). Laboratory data were analyzed using SPSS 23 ANOVA and further tested using Duncan's test. Statistical analysis revealed no significant differences (P > 0.05) in protein profiles between F1 LLI and F1 BLI. However, F1 calves from the crossbreeding differed significantly (P < 0.05) from the LI dam in total protein and globulin, except for albumin, which showed no significant difference (P > 0.05). The conclusion of this study is that the protein profiles of F1 LLI and F1 BLI are not significantly different, but F1 LLI shows a tendency toward higher total protein and albumin levels and lower globulin levels. Both F1 crossbreeds have significantly lower total protein and globulin levels compared to the Limousin Indonesia parent, with albumin levels also tending to be lower.